Building professional identities as English language teachers with Islamic spiritual values through collaborative digital storytelling - Fikri Yanda (Indonesian Reseacher for Language Learning and Teaching, 2026)
Drawing on a larger virtual ethnography study, this case study research examined how digital storytelling affected preservice teachers’ professional identity construction as future English teachers with Islamic spiritual values. Within the context of online learning during the COVID-19 pandemic, preservice teachers completed movie watching and digital storytelling projects in which they were required to compose and design digital narratives based on their movie watching experiences, reflect during the process, and consider the Islamic values they have learned from the movies within the digital videos they made. Data were collected from 17 teacher candidates from an English language teacher education program in Indonesia and analyzed using qualitative methods. Findings showed that preservice teachers’ experiences with making their own digital stories contributed to their developing professional identities as teachers and shaped their perceptions about how to become better English teachers with Islamic backgrounds.